Model Innovation dalam Meningkatkan Daya Saing UMKM di Era Digital - Dede Yusuf Sutrisman; Jeni Susyanti (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2025)
The rapid advancement of the digital era has presented both opportunities and challenges for Micro, Small, and Medium Enterprises (MSMEs) to innovate their business models. This study aims to analyze the role of Business Model Innovation (BMI) in enhancing the competitiveness of MSMEs during the ongoing digital transformation. A literature review method was employed, drawing upon a variety of academic sources. The findings reveal that applying BMI through the adoption of digital technologies—such as e-commerce platforms, social media, and fintech—can boost MSME revenues by 25–30%, expand market reach, and strengthen business resilience. However, the adoption of BMI still encounters several obstacles, including low levels of digital literacy (with only 35% of MSMEs proficient in using digital tools), limited access to financing, and uneven infrastructure development.